Autophagy in aging-related oral diseases - Peña-Oyarzún, Daniel; San Martin, Carla; Hernández-Cáceres, María Paz; Lavandero, Sergio; Morselli, Eugenia; Budini, Mauricio; Burgos, Patricia V.; Criollo, Alfredo (Frontiers in Endocrinology, 2022)
Autophagy is an intracellular degradation mechanism that allows recycling of organelles and macromolecules. Autophagic function increases metabolite availability to the control of metabolic pathways, differentiation and cell survival. The oral environment is composed of several structures, including mineralized and soft tissues which are formed by complex interactions between epithelial and mesenchymal cells. With aging, increased prevalence of oral diseases such as periodontitis, oral cancer and periapical lesions is observed in humans. These aging-related oral diseases are chronic conditions that alter the epithelial-mesenchymal homeostasis, disrupting the oral tissue architecture affecting the quality of life of the patients. Given that autophagy levels are reduced with age, the purpose of this review is to discuss the link between autophagy and age-related oral diseases.